In-situ Rice (Oryza sativa) Stubble Management in Preparing Paddy Land for the Next Crop in Brahmaputra Valley - Manas Jyoti Barooh; Amarjyoti Khound (International Journal of Economic Plants)
The experiment was conducted during October, 2019 at Neul Gaon, Jorhat, Assam, India to evaluate the performance of a tractor-operated paddy straw chopper and its effect on straw incorporation into the soil. The chopper, operated using a 55 hp Eicher 855FE tractor, was tested in two gear settings (L2 and L3). The chopper’s effective working width was 2.1 meters, with an effective field capacity of 0.67 hectares per hour. The chopped straw was analyzed for its length, with the L3 gear producing smaller pieces (89.1% in the 0-20 cm range). The study further investigated the weight reduction of chopped straw after incorporation into the soil using two implements: a rotavator and a tyne tiller, both tilling to a depth of 8 cm. The incorporation was assessed two weeks after straw placement, revealing an average weight reduction of 37.36% for the tyne tiller and 36.20% for the rotavator. These findings suggest that the tractor-operated paddy straw chopper, when used in combination with post-chopping incorporation techniques, effectively reduces straw size, thereby promoting quicker decomposition. The smaller straw particles enhance microbial activity, contributing to improved soil quality and faster organic matter breakdown. This approach offers a sustainable solution for straw management in rice farming, helping reduce field residue, improve soil conditions, and support the overall sustainability of rice cultivation systems.